Analysing The Interest In Buying Electric Motorbikes In The Community In Jakarta - Sriyono, Muhammad Bagus; Sholikhah; Agustin Pratama Sari, Dewi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyse the Technology Acceptance Model (TAM) on the interest in buying electric motorbikes in DKI Jakarta. TAM is a model used to understand how users accept and use new technology. This model involves several main dimensions, such as Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude (A). This research uses purposive sampling method for sample selection. The analysis techniques applied include descriptive analysis and average score calculation. The results showed that the Attitude Towards dimension received an average score of 3.37 which was included in the "strongly agree" category and was in the very highlevel interval. The Perceived Ease of Use dimension obtained a score of 3.37 which is in the high interval scale range. Meanwhile, Perceived Usefulness received a score of 3.30 which is also in the very highlevel interval. Of the three dimensions, Attitude Towards has the highest effectiveness value, followed by Perceived Ease of Use, and then Perceived Usefulness. This suggests that a positive attitude towards electric motorbikes is the most powerful factor influencing purchase intention, followed by ease of use and perceived usefulness. The implications show that the factors that influence the purchase interest of electric motorbikes can be measured using TAM, which plays an important role in measuring purchase interest in the Jakarta community. In addition, the results of this study can also serve as a basis for the government in designing policies that support the use of electric motors, such as tax incentives or subsidies for the purchase of electric motors.